A DESCRIPTION OF CHARACTERISTICS OF BLOOD DONORS THAT PASSED THE SELECTION OF DONORS IN THE INDONESIAN BLOOD TRANSFUSION UNIT, GUNUNGKIDUL DISTRICT - Tasya Karolina (Akper Kesdam I/Bukit Barisan Padang, 2021)
Background: Characteristics of voluntary blood donors and substitute donors include age. Gender, blood group, rhesus blood type and donor type play an important role in the selection of blood donors. These characteristics support the awareness and desire of people who are not willing to become donors, because they do not know the benefits of donors for health. Research Objectives: To know the description of the characteristics of blood donors who passed the donor selection at UTD PMI Gunungkidul 2020, including the characteristics of donors based on age, gender, blood type, rhesus type and type of donor Research Methods: This type of descriptive quantitative research is to describe the research data with a cross-sectional study approach, namely the research design study within a certain time frame and the time has been determined by the researcher. Research Results: There were 368 donors in 2020, using simple random sampling, with the results on the characteristics in the Age group 25-44 with a total of 194 (52.6%), in the Gender group there were men with a total of 296 (80.5%), Blood type for Blood Type O with a total of 132 (35.8%), based on Rhesus Type, there were Rhesus Positive with a total of 367 (99.9%), and for the Type of Donor Type of Voluntary Donor with a total of 328 (89.1%). Conclusion: With more groups aged 25-44 years, Male Gender, Blood Type O, Positive Rhesus Type and Type of Voluntary Donors